Dropout, Autonomy and Reintegration in Spain: A Study of the Life of Young Women on Temporary Release - Añaños, Fanny T.; García-Vita, María del Mar; Galán-Casado, Diego; Raya-Miranda, Rocío (Frontiers in Psychology, 2020)
This study analyses the psycho-educational and social paths of women prisoners after the time they drop out of school as minors, based on different variables related to autonomy and their preparedness to face temporary release. Methods Qualitative and quantitative methods were used to analyse a national sample of 310 women prisoners (30.1% of the population) in 31 prisons through a mixed-mode questionnaire and interview. We analysed the significant association of variables related to dropout and obtained a log-linear model that relates dropout to recidivism and Roma culture. Work experience was analysed using the McNemar test, and variables influencing the participant’s job at the time of the study were analysed by applying cluster analysis. Results Young women comprise 66.6% of individuals who drop of the education system as minors (primary 49.3% and secondary 22%). They drop out between the ages of 7 and 17, and have traits of greater vulnerability than those who stayed in school until adulthood. In this population, we find a significant association with various factors: belonging to Roma culture, having family members in prison and delinquent recidivism; and higher unemployment (43.4%) and low income before entering prison. This situation is increasing today. In prison, these women had more connection to education/training, which can improve their employability. They also encounter difficulties with personal security, decision-making, personal/professional dependence, planning for the future, administrative matters and handling information and communication technologies, job-seeking skills, etc. Their self-perceived strengths are, however, assuming responsibility, taking orders, respecting schedules and timetables, working on a team and feeling prepared to start a job, as well as having optimistic convictions about the future. Conclusion The vulnerabilities and risk factors studied have a negative influence primarily on processes of personal, social and job autonomy in female minors who left the education system. Yet these minors show factors of protection and resilience. On temporary release at the time of the study, they face the consequences that their prison terms and incarceration have for their perceptions, attitudes, competencies and future prospects, as well as social marginalization and stigma. Early, coherent socio-educational interventions are thus needed to improve social integration-reintegration.